PEMETAAN PRODUK ANDALAN SEKTOR PERTANIAN DI KABUPATEN MUKOMUKO - Cahyadinata, Indra (Jurnal AGRISEP, 2008)
Data of PDRB Mukomuko District indicates that contribution of agricultural sector up to 50.7%. That means, agricultural sector is one of the sectors able to be made as bases in development of Mukomuko. This Research aim is to cluster of agricultural product that is able to be developed as bases product and to study of feasibility of agricultural product. Research results indicate that food crop become bases in three sub-districts (Lubuk Pinang, Teras Terunjam and Pondok Suguh), animals breeding  become bases in three sub-districts (Lubuk Pinang, Mukomuko Utara and Mukomuko Selatan), fishery become bases at three sub-districts (Mukomuko Utara, Mukomuko Selatan and Pondok Suguh) and plantation sub-sector become bases at all of sub-districts. Financially, all farming type can be categorized a feasible, but its business (not include palm) is small scale, so the earnings is unable to fulfill requirement of household consumption.